CH3NH3PbBr3 Thin Film Served as Guided-Wave Layer for Enhancing the Angular Sensitivity of Plasmon Biosensor - Leiming Wu; Yuanjiang Xiang; Yuwen Qin (Biosensors, 2021)
CH3NH3PbBr3 perovskite thin film is used as a guided-wave layer and coated on the surface of an Au film to form the Au-perovskite hybrid structure. Using the hybrid structure, a perovskite-based guided-wave surface plasmon resonance (GWSPR) biosensor is proposed with high angular sensitivity. First, it is found that the electric field at the sensing interface is improved by the CH3NH3PbBr3 perovskite thin film, thereby enhancing the sensitivity. The result demonstrates that the angular sensitivity of the Au-perovskite-based GWSPR biosensor is as high as 278.5°/RIU, which is 110.2% higher than that of a conventional Au-based surface plasmon resonance (SPR) biosensor. Second, the selection of the coupling prism in the configuration of the GWSPR biosensor is also analyzed, and it indicates that a low refractive index (RI) prism can generate greater sensitivity. Therefore, the low-RI BK7 prism is served as the coupling prism for the proposed GWSPR biosensor. Finally, the proposed GWSPR sensing structure can not only be used for liquid sensing, but also for gas sensing, and it has also been demonstrated that the GWSPR gas sensor is 2.8 times more sensitive than the Au-based SPR gas sensor.